2006
DOI: 10.1037/0022-3514.91.6.1123
|View full text |Cite
|
Sign up to set email alerts
|

Helping one's way to the top: Self-monitors achieve status by helping others and knowing who helps whom.

Abstract: The authors argue that high self-monitors may be more sensitive to the status implications of social exchange and more effective in managing their exchange relations to elicit conferrals of status than low self-monitors. In a series of studies, they found that high self-monitors were more accurate in perceiving the status dynamics involved both in a set of fictitious exchange relations and in real relationships involving other members of their social group. Further, high self-monitors elevated their social sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
428
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(446 citation statements)
references
References 61 publications
(64 reference statements)
13
428
4
1
Order By: Relevance
“…Status-related motivations have a profound effect on individuals' social behavior, personal goals, relationships with others, and major life decisions (e.g., Flynn et al, 2006;Fodor & Farrow, 1979;Kasser & Ryan, 1993). Yet very little attention has been given to the origins of such motivations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Status-related motivations have a profound effect on individuals' social behavior, personal goals, relationships with others, and major life decisions (e.g., Flynn et al, 2006;Fodor & Farrow, 1979;Kasser & Ryan, 1993). Yet very little attention has been given to the origins of such motivations.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, individuals' beliefs about whether they provide value to a group are centered on whether they think they possess skills and capacities important to a group's success. Therefore, self-efficacy beliefs concerning the specific abilities that enable the group to succeed shape overall self-perceptions of value to the group (Berger et al, 1972). considering the important role status striving plays in directing behavior (Flynn et al, 2006;Frank, 1985;Kasser & Ryan, 1993). Finally, these studies are the first to examine whether individuals' pursuit of status rank is context dependent.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…So, for example, Van der Vegt, Bunderson, & Oosterhof (2006) found that group members were more likely to help other group members who were above them in the status hierarchy but not below. Research by Flynn, et al (2006) and Flynn (2003) provides one possible explanation for this finding by suggesting that interpersonal helping may be as much about status enhancement as knowledge transfer; helping a higher status member is more status-enhancing than helping a lower-status member. Moreover, research by Lee (1997) suggests that status can also affect help-seeking behavior.…”
mentioning
confidence: 99%
“…However in the laboratory context, we expected verbal skills to be a critical social skill-more important than, for instance, the ability to learn a social network (Flynn, Reagans, Amanatullah, & Ames, 2006). Participants thus ranked the group members on how verbally skilled they were.…”
Section: Peer-ranked Social Skillmentioning
confidence: 99%